สถานะ อำนาจหน้าที่และความเป็นอิสระขององค์กรกำกับดูแล: ศึกษาเปรียบเทียบกรณีคณะกรรมการกำกับกิจการพลังงาน กับ คณะกรรมการกิจการกระจายเสียง กิจการโทรทัศน์และกิจการโทรคมนาคม - สรรญกฤต ศรีสงสาร (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Energy and telecommunication industry are the fundamental infrastructure in every country.With the upcoming inauguration of the free trade, the state who once used to monopolize the industry of public services in relation to energy and telecommunication, is required to allow private sectors to take part in the management only where the competition is needed . As for the public-security related to services , State still withhold the administration there of in order to allow free and fair competition it is important to have a free and independent organ to control the procedureThis is a comparative study on status, competence and autonomy of controlling organization in public utility founded in Thailand, namely the Energy Regulatory Commission and the National Broadcasting and Telecommunication Commission. Both of them has more or less the same status, competence and autonomy. But many aspects of these resemblances and differences deserve to be studied.The study show that ,despite the function of both supervising organ in the management of such infrastructure . the detail regarding status , power and independence are different . On one hand the National Broadcasting and Telecommunication Commission concentrates its power to conduct policy and its supervising function in one organ . It seems,thus, more competent and independent. On the other hand , the Energy Regulatory Commission only has power to supervise . The power to supervise . The power to conduct policy regarding energy is conferred to the government . Its independence is limited because of this connection with the government.